"PARA LA PAZ PERPETUA" DE KANT Y EL "FUNDAMENTO DEL DERECHO NATURAL" DE FICHTE: ENCUENTROS Y DESENCUENTROS - Oncina, Faustino (Daimon Revista Internacional de Filosofia, 1994)
In the Foundation of Natural Right Fichte showed that his three sources of inspiration were S. Maimon, J. B. Erhard and Kant's The Perpetual Peace. IN 1796 Fichte wrote a review of Kant's work, in which he anticipated some of the ideas of this book. This paper analises the following three aspects that are common to this review and Foundation of Natural Right: 1) The emancipation of right with respect to moral. 2) The relation between right and history. 3) The role of publicity in the concept of republican democracy. It is precisely his misunderstanding of the kantian spirit what propiciates the transition from Enlightenment to Romanticism.